Optimasi Agribisnis Pangan sebagai Strategi Peningkatan Ekonomi Masyarakat di Kabupaten Bireuen - Naziratil Husna; Dini Annisha (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Empowering the local economy is important to create sustainable development. Food commodities are one of the most strategic sectors with excellent development potential. The food sector is important not only to meet the needs of the community but also to be a sector that has a positive impact on creating prosperity, creating jobs, and supporting long-term economic development. This study aims to reduce the gap between more developed and underdeveloped regions and to find the right alternative strategies to optimize efforts in the food sector. This research was conducted from August to September 2024 in Alue Ketapang Village, Hagu Village, and Lawang Village, Bireuen Regency, Aceh Province. The number of respondents in this study was 92 people. Several variables studied were a village's strengths, weaknesses, opportunities, and threats. The research method uses a purposive method with a qualitative descriptive approach. The data analysis method uses SWOT analysis and IFAS and EFAS analysis. The results of this study are the S-O strategy, which is in the first quadrant, an aggressive growth strategy (growth-oriented strategy). Very underdeveloped villages in Bireuen Regency have the potential to develop both in terms of natural resources and human resources. With an integrated approach involving the community in every step of planning and supported by government and private sector policies, these villages can optimize their potential to improve community welfare and advance the local economy. It is important to ensure that every strategy implemented is relevant to local needs and characteristics and is sustainable.